Análisis del diálogo en "Le Prince Corsaire" de Scarron - Ruiz Álvarez, Rafael (Estudios Humanísticos. Filología, 1988)
El presente artículo, como su título indica, tiene como objeto primordial el análisis del diálogo en Le Prince Corsaire, tragicomedia del siglo XVII, perteneciente a P. Scarron. Dicho análisis está basado no sólo en la descripción de la forma y el tema de las estructuras dialogadas, sino también en la relación que existe entre éstas y la estructura actancial dentro del marco de la comunicación, así como de las condiciones de producción de dicho diálogo. Las conclusiones a las que hemos llegado demuestran que la obra de Scarron, considerada desde el punto de vista del diálogo, presenta a unos actores perfectamente tipificados, que, sometidos a unas leyes sociales determinadas dentro de una época, se mueven en un contexto en el que las relaciones aparecen como algo sistematizado tanto en su modo de concepción como en el de la expresión. Uno y otro modo están íntimamente ligados a la forma y al contenido del diálogo, considerado como mensaje dentro del acto de comunicación en el que participan los mencionados actores. This article, as its title suggests, a primarily concerned with the analysis of the dialogue in Le Prince Corsaire, a seventeenth century tragicomedy by P. Scarron. The analysis does not simply deal with a description of the form and subject matter of the dialogue, but also how these fit finto the structure of «actants», within the overall framework of communication, that is to say, the conditions which make up the dialogue. First we have dealt with the relationship between characters and dialogues, the form content of these dialogues, while at the same time examining the part playcd by the structure of the acts, in the ultimate aim of communication. Then, using the results which we have obtaincd from this method of analysis, we have tried to put into perspective the effect which can be achieved by the use of a certain type of dialogue in order to examine more clearly the significance of the communicative structure. The conclusions wc have reached demonstrate that Scarron's play, at least from the angle of dialogue, presents severa! perfectly sterio-typical characters, who, subject to certain set social rules of the time, move within a context in which relationships appear rather systematic, both in the perception and the expression of the relationships by the characters. This is apparent in the form and content of the dialogue, rather like a message within the action of communicating, in which the characters participate.